Translating Western Social and Human Sciences in Argentina: A Comparative Study of Translations from French, English, German, Italian and Portuguese - Sora, Gustavo Alejandro (2018)
This chapter analyzes the translations of social sciences and humanities books in Argentina from 1990 to 2011. Argentina occupies a doubly peripheral position in the global system of symbolic production. Its language, Spanish, is peripheral in comparison to English, and, although to a lesser extent, to French and German. Second, scientific and cultural geopolitics indicate that the United States and Europe are the main producers and communicators in all scientific areas. The choice of studying translations in Argentina is not only theoretical -margins are key to understanding the centers- but also empirical. Based on the analysis of bibliographical statistical data and of a series of interviews, this study compares the volumes and dynamics of French, English, German, Italian and Portuguese translations, and explores the system of conditions that leads publishers to prefer certain languages before others, as well as the ways in which the structure and functioning of the publishing field have effects on the valuation of the intellectual production of different languages and countries. The first finding is the longstanding primacy, which continues to the present, of French in the translation of social sciences and humanities books.